Regulation and Significance of Sharia Economic Dispute Resolution in Religious Courts - Heris Suhendar; Yadi Janwari (Jurnal Ilmu Hukum Tambun Bungai, 2023)
Religious courts have a function as actors of independent judicial power at the first level to administer justice to uphold law and justice. To carry out their functions, religious courts are given the duty and authority to examines, decide and resolve cases at the first instance between people of the Islamic faith, one of which is in the field of sharia economics. The urgency of this research is to explain and analyse the implementation of Radbruch's legal objectives in the trial process, so as to produce a fair and certain court decision. Therefore, this research aims to examine the regulation and significance of the settlement of sharia economic disputes in the Religious Courts. This research is a doctrinal research that examines the law conceptualised as a rule, using conceptual approaches and legislation. The results of the study found that: 1) the regulation of economic dispute resolution comes from legislation, customs, and jurisprudence; and 2) the significance of sharia economic dispute resolution in the Religious Courts, namely the obtaining of justice, finality / usefulness, and legal certainty for the justice-seeking community.